2023
DOI: 10.3390/foods12203718
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Microbial Diversity and Hygienic-Sanitary Status during Processing of Farmed Rainbow Trout (Oncorhynchus mykiss)

Salud María Serrano Heredia,
Javier Sánchez-Martín,
Verónica Romero Gil
et al.

Abstract: Aquaculture is becoming a strategic sector for many national economies to supply the increasing demand for fish from consumers. Fish culture conditions and processing operations can lead to an increase in microbial contamination of farmed fish that may shorten the shelf-life of fish products and byproducts, and ready-to-eat fishery products. The objective of this study was to evaluate the hygienic-sanitary status of water, environment, and processing of fresh-farmed rainbow trout (Oncorhynchus mykiss) fillets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The microbiota in the processing facility, where bacteria encounter temperatures ranging from −20°C to +70°C and significant moisture, was dominated by Pseudomonas , Acinetobacter and Exiguobacterium . While Exiguobacterium is often found in extreme environments ( Vishnivetskaya et al, 2009 ), Pseudomonas and Acinetobacter are commonly found in diverse food processing environments ( Zwirzitz et al, 2021 ; Rolon et al, 2023 ; Serrano Heredia et al, 2023 ; Tadielo et al, 2023 ; Valentino et al, 2023 ; Xu et al, 2023 ). In addition, members of Pseudomonas ( Zhang et al, 2019 ; Chauhan et al, 2023 ), Acinetobacter ( Kim et al, 2018 ; Herrera et al, 2021 ) and Exiguobacterium ( Vishnivetskaya et al, 2007 ; Rodrigues et al, 2008 ) are capable of adapting to low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota in the processing facility, where bacteria encounter temperatures ranging from −20°C to +70°C and significant moisture, was dominated by Pseudomonas , Acinetobacter and Exiguobacterium . While Exiguobacterium is often found in extreme environments ( Vishnivetskaya et al, 2009 ), Pseudomonas and Acinetobacter are commonly found in diverse food processing environments ( Zwirzitz et al, 2021 ; Rolon et al, 2023 ; Serrano Heredia et al, 2023 ; Tadielo et al, 2023 ; Valentino et al, 2023 ; Xu et al, 2023 ). In addition, members of Pseudomonas ( Zhang et al, 2019 ; Chauhan et al, 2023 ), Acinetobacter ( Kim et al, 2018 ; Herrera et al, 2021 ) and Exiguobacterium ( Vishnivetskaya et al, 2007 ; Rodrigues et al, 2008 ) are capable of adapting to low temperatures.…”
Section: Discussionmentioning
confidence: 99%